Efficacy and safety of angiogenesis inhibitors in melanoma: a meta-analysis of seven randomized controlled trials. Issue 3 (29th March 2022) - Fu, Xue-Lei; Feng, Li-Ping; Yu, Hai-Rong; Du, Lin; Song, Yi-Ping; Chen, Hong-Lin
Abstract : Little is known about the efficacy and safety of angiogenesis inhibitor therapy in patients with melanoma. The objective of this study was to assess the possible benefits and harms of angiogenesis inhibitor therapy in patients with melanoma. Electronic databases of PubMed and Web of Science were searched from inception to January 2020. Randomized controlled trials (RCTs) that investigated the efficacy and safety of angiogenesis inhibitor therapy in patients with melanoma were included. Primary outcomes were overall survival (OS) and progression-free survival (PFS), reported as hazard ratios (HRs). Secondary outcomes were disease control, objective response, and adverse events, reported as odds ratios (ORs), and trial sequential analysis (TSA) was also performed. We identified seven trials with 3185 patients. There was no significant difference in OS [HR, 0.99; 95% confidence interval (CI), 0.90–1.09] or PFS (HR, 0.91; 95% CI, 0.83–1.00) between the treatment groups. No significant effect of angiogenesis inhibitor therapy was identified on disease control (OR, 1.23; 95% CI, 0.97–1.55) or objective response (OR, 1.27; 95% CI, 0.99–1.62). TSA showed that the sample size for analysis of disease control was sufficient. Additionally, angiogenesis inhibitor therapy increased risks of hypertension, neurological symptoms, and diarrhea. Angiogenesis inhibitor therapy makes no significant improvement in OS or PFS in patients with melanoma and even causes an increased risk of important adverse events. Therefore, angiogenesis inhibitor therapy is not recommended for the treatment of melanoma.